Sexual and Reproductive Health Needs of HIV-Positive People in Tehran, Iran: A Mixed-Method Descriptive Study - Saharnaz Nedjat; Babak Moazen; Farimah Rezaei; Shayesteh Hajizadeh; Reza Majdzadeh; Hamid Reza Setayesh; Minoo Mohraz; Mohammad Mehdi Gooya (Kerman University of Medical Sciences, 2015)
Background People Living with HIV (PLHIV) are highly stigmatized and consequently hard-to-access by researchers and importantly, public health outreach in Iran, possibly due to the existing socio-cultural situation in this country. The present study aimed to evaluate the sexual and reproductive health needs of PLHIV in Tehran, the capital of Iran. Methods As a mixed-method descriptive study, this project was conducted in 2012 in Tehran, Iran. In this study, we evaluated and discussed socio-demographic characteristics, family and social support, sexual behaviors, fertility desires and needs, PMTCT services, contraceptive methods, unintended pregnancy and safe abortion, and Pap smear tests among 400 participants referring to the behavioral disorders consulting centers. Results Of the sample 240 (60%) were male and 160 (40%) were female. About 50% of women and 40% of men were 25-34 years old. More than 60% of men and 96% of women were married, while more than 50% of the participants had HIV-positive spouses at the time of study. According to the results, fertility desire was observed among more than 30% of female and 40% of male participants. Results of the in-depth interviews indicate that the participants are not satisfied with most of the existing services offered to address their sexual and reproductive health needs. Conclusion Despite the availability of services, most of sexual and reproductive health needs of the PLHIV are overlooked by the health system in Iran. Paying attention to sexual and reproductive health needs of PLHIV in Iran not only protects their right to live long and healthy lives, but also may prevent the transmission of HIV from the patients to others within the community.